Food consumption behavior and lifestyle changes among rural older adults before and during the COVID-19 pandemic in northern India: a cross-sectional study - Verma, Ashish Kumar; Annapurna; Panchgaur, Richa; Kumar, Alok (International Journal Of Community Medicine And Public Health, 2023)
Background: Due to COVID-19, the lockdown was imposed throughout the nation on 24 march 2020 and COVID-19 is not over yet, cases are still coming. Food insecurity was already a problem but it became even more challenging during the pandemic. Especially rural older adult people have had to deal with the problem of food and health-related issues due to the pandemic. This study aimed to assess food consumption behavior and lifestyle changes among rural older adults before and during the COVID-19 pandemic. Methods: A retrospective cross-sectional study has been conducted in rural areas of the Varanasi district, Uttar Pradesh through personal interviews; a multistage random sampling technique was used to select the participants. 450 participants were taken aged 60 and above for final analysis. The McNemar and Wilcoxon sign rank tests were used to examine differences before and during the COVID-19 pandemic, adopting the statistical significance of p<0.05. Results: 66.0% of people faced a shortage of food. 40.9% of people reported that they had reduced their food intake. 27.6% of participants reported a reduction in body weight. There was a significant percentage decrease in consumption of milk products, pulse, and green vegetables (p<0.001), a percentage decrease in initiating and maintaining sleep (p<0.001), and worse health conditions (p<0.001). Conclusions: Food consumption behavior and lifestyles have changed significantly during the COVID-19 pandemic among rural older adults.